The social and ethical issues faced by chronically ill female cancer patients - Baba, Mudasir Rashid; Buch, Sajad Ahmad; Sabet, Negar Shafiei; Doustjalali, Saeid Reza; Soundararajan, Leo Rathinaraj Antony; Oo, Khin Thane; Thawda Oo, Mon Mon; Shahani, Muhammad Parial; Haque, Shahnaz; Bidin, Mohd Zin; et al. (Journal of Neonatal Surgery, 2025)
This study examines and explains the impact of chronic illness on the social fabric and related ethical issues in female cancer patients. Sixty female patients from the medical oncology department from private medical college Hospital participated in this study. The data was collected from responses to a self-administered validated questionnaire comprising of 5 domains. The 5 domains used were i) Dependency ii) Communication iii) Issues with gender iv) Hesitancy regarding personal acts and, v) Emotional components. The domains were used and social and ethical issues were dissected out. The response to most of the domains consisting queries regarding autonomy and dignity in this study was moderate. A significant proportion of the participants however, showed concern in emotional domain with 70% being forced to spend time in bed during episodes of pain and 73.3% fearing to lose hope if left alone during their illness. This study emphasized the importance of social and ethical issues arising from chronic illness like cancer.